2012
DOI: 10.1039/c2jm16901k
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched-polymer functionalization of graphene sheets for enhanced mechanical and dielectric properties of polyurethane composites

Abstract: The incorporation of graphene sheets (GSs) into polymer matrices affords engineers an opportunity to synthesize polymer composites with excellent physical performances. However, the development of high performance GS-based composites is difficult because of the easy aggregation of GSs in a polymer matrix as well as the weak interfacial adhesion between GSs and the host polymer. Herein, we present a simple and effective route to hyperbranched aromatic polyamide functionalized graphene sheets (GS-HBA). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(127 citation statements)
references
References 63 publications
(94 reference statements)
7
115
0
Order By: Relevance
“…For G-ODA, the appearance of new characteristic absorption peaks (ANHA, ACNA) indicates ODA has been grafted successfully onto the graphene sheet. This result is agreeable with the previous report [12]. Figure 1b compares the FTIR of GO, ODA, rG-ODA, and rGO.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…For G-ODA, the appearance of new characteristic absorption peaks (ANHA, ACNA) indicates ODA has been grafted successfully onto the graphene sheet. This result is agreeable with the previous report [12]. Figure 1b compares the FTIR of GO, ODA, rG-ODA, and rGO.…”
Section: Resultssupporting
confidence: 94%
“…Especially for polar polymers, for example, polyurethane (PU) [12][13][14], poly(butylene terephthalate) [15], and epoxy resin [16,17], because some interactions would take place between oxygen-containing functional groups on the GO surface and polymer matrix. However, the application of GO in non-polar polymers is limited because they are incompatible.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have demonstrated that the increase in k is far less than that expected using GO as the dielectric filler because of the severe disruption of the graphite structure of GO [41]. Therefore, the reduction of GO@SiO 2 /PDMS composites is required to increase the interfacial polarization ability of GO@SiO 2 .…”
Section: In Situ Thermal Reduction Of Go@sio 2 /Pdmsmentioning
confidence: 99%
“…3 that GO was not thermally stable. Its major mass loss appeared in the temperature range from 150°C to 300°C, associated with pyrolysis of the massive labile oxygen functional groups on its surface [33]. In contrast, the total mass loss of FGO could be divided into two major stages.…”
Section: Characterization Of Fgo and Gomentioning
confidence: 99%
“…After chemical functionalization of GO with MDI and PCL, the amount of available hydrogen-bond donor groups decreased significantly, thus weakening the interlayer interactions in FGO, which contributed to the exfoliation of FGO in the DMF solvent. Meanwhile, the covalently grafted MDI and PCL on the surface of the FGO sheets could effectively prevent the graphene backbones from direct contact [33], which was also beneficial to the exfoliation of FGO in the solvent.…”
Section: Dispersions In Solvent and Pu Matrixmentioning
confidence: 99%